Multivariable Generalized Predictive Control Using An Improved Particle Swarm Optimization Algorithm - Sedraoui, M.; Abdelmalek, S.; Gherbi, S. (Informatica)
Multivariable Generalized Predictive Control Using An Improved Particle Swarm Optimization Algorithm